Optimal Operation of Active Distribution Systems with Voltage Control and Closed-Loop Topology - Home-Ortiz, Juan M.; Macedo, Leonardo H.; Mantovani, Jose R. S.; Romero, Ruben; Vargas, Renzo; Catalao, Joao P. S. (2021 IEEE Madrid PowerTech, 2021)
This paper presents a new stochastic mixed-integer second-order cone programming model to solve the problem of optimal operation of distribution systems considering network reconfiguration, voltage control devices, dispatchable and nondispatchable distributed generators (DGs), and the possibility of closed-loop topology operation. The decision variables are the active and reactive power generation of DGs, the tap position of substations' (SS) on-load tap changers and voltage regulators, the number of switchable capacitor banks in operation, and the operational statuses of sectionalizing and tie switches. The proposed formulation considers the minimization of (i) the cost of the energy purchased from the distribution SSs and dispatchable DGs, (ii) greenhouse gas emissions, (iii) technical energy losses, and (iv) the number of basic loops formed in the network. Tests are carried out using the 33-node system and the results demonstrate the effectiveness of the proposed formulation. The benefits provided by the presented approach include reduced operational costs and greenhouse gas emissions mitigation.